Shared features of successful interorganizational collaboration to promote local talent development environments in Denmark - Mathorne, O.; Stambulova, N.; Book, R.; Kamuk Storm, L.; Henriksen, K. (Scandinavian Journal of Sport and Exercise Psychology, 2021)
The aim of this study was to explore 11 case examples of successful talent development collaborations between sport federations, municipalities, and local clubs in Denmark in order to identify potential shared features of successful collaborations. We hypothesized that each case example would be unique, but that they would also share features that could be organized to provide practitioners with a model to guide the improvement of their practice. Grounded in the holistic ecological approach, the study was designed as a multiple case study to facilitate a cross-case analysis. Three Danish sport federations (handball, ice hockey, and swimming), nine municipalities, and eleven local clubs participated in the study, and the data was generated from 23 semi-structured interviews with stakeholders. Analysis led to the construction of six shared features of successful interorganizational collaboration organized into: (1) a list of features (SFIC-TD) with positive and opposite pole descriptors and three categories: collaborative philosophy, collaborative decisions, and collaborative actions, and (2) an applied framework termed the pyramid model for optimization of interorganizational collaboration in talent development (PIC-TD) which illustrates how the abovementioned categories lead to collaborative outcomes. Developing a shared philosophy of talent development was found to be a foundational starting point for successful collaboration between relevant organizations on the micro- and macro-level to improve the local athletic talent development environment.